Variants within the nitric oxide synthase 1 gene are associated with stroke susceptibility - Manso, H. (2012)
Animal studies have allowed important insights into the role of the nitric oxide synthase (NOS) enzymes in atherosclerosis and hypertension, as well as in stroke. In this study we tested the hypothesis that the NOS1 and NOS3 genes, respectively encoding neuronal NOS (nNOS) and endothelial NOS (eNOS), influence stroke susceptibility and outcome after a stroke event.